E-042 Case Based Review of the Pathophysiology of Internal Carotid Artery Pseudoaneurysm Coil Migration. (14th July 2013) - Morgan, R; Best, S; Connor, C; Madarang, J; Johnson, P
Abstract : Learning Objectives: Review the pathophysiology and risk factors of internal carotid artery (ICA) pseudoaneurysm formation. Evaluate imaging of coil migration following endovascular treatment of internal carotid artery pseudoaneurysm. Discuss treatment options of coil migration. Background: Pseudoaneurysm results from disruption of one or more layers of the arterial wall, which results in blood dissecting into the surrounding tissues. The formation of ICA pseudoaneurysm is a known complication related to radiation therapy and arterial injury during surgery. Endovascular coil embolisation has been proven an effective treatment for ICA pseudoaneurysm, however one of the rare complications is coil migration. Clinical Findings/Procedure Details: Two patients with history of iatrogenic ICA injury during tumour resection subsequently developed pseudoaneurysms. Both were initially treated with endovascular coil embolisation and both went on to suffer migration and prolapse of the coil into the pharynx. In both cases the coil mass demonstrated migration with erosion through the pseudoaneurysm wall. The first patient underwent coil embolisation 20 years prior to presenting with globus sensation and epistaxis. The second patient, who had previously been treated with radiation, developed transmucosal coil migration 1 month after embolisation. In both cases the complications associated with coil migration were fatal. Conclusion and/or Teaching Points: When treating ICA pseudoaneurysm with coil embolisation there are multiple factors which can increase the risk of coil migration. While it is rare coil migration is a known complication of endovascular embolisation which can occur months to decades after the initial procedure. Disclosures: R. Morgan: None. S. Best: None. C. Connor: None. J. Madarang: None. P. Johnson: None.